(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The emergence of Industry 5.0 marks a paradigm shift from the technology-centric ethos of Industry 4.0 to a more inclusive, human-centric approach, which emphasizes collaboration between humans and intelligent systems. As manufacturing systems evolve into complex cyber-physical ecosystems, the integration of Human-Centric Design (HCD) becomes essential for ensuring not only operational efficiency but also social sustainability, resilience, and adaptability. This paper proposes a comprehensive framework for the integration of HCD principles into smart manufacturing systems, with the aim of fostering resilience and enhancement of worker well-being in the context of Industry 5.0. Through a multidisciplinary synthesis of literature spanning human factors engineering, cyber-physical systems, and organizational design, the study identifies key enablers such as collaborative robotics, AI-driven decision support, ergonomic workplace design, and adaptive human-machine interfaces. The proposed framework emphasizes the co-evolution of human and machine capabilities, promotion of shared autonomy, skill augmentation, and cognitive load management. Furthermore, it outlines mechanisms for embedding ethical considerations, inclusivity, and stakeholder participation into design processes. Case studies and recent empirical research were analyzed to validate the framework’s applicability and to demonstrate its potential in the improvement of system resilience, during disruptions such as supply chain disturbances and workforce shifts. The findings underscore that a human-centric approach not only enhances technical robustness and responsiveness, but also empowers workers, and leads to higher levels of engagement, creativity, and organizational agility. This study contributes to the emerging discourse on Industry 5.0 by offering a structured pathway for aligning advanced manufacturing technologies with human values. The proposed framework serves as a strategic guide for policymakers, engineers, and organizational leaders that aim at building future-ready, human-aligned manufacturing systems.